2019
DOI: 10.1002/ente.201900515
|View full text |Cite
|
Sign up to set email alerts
|

Pyroelectric Energy Conversion in Doped Hafnium Oxide (HfO2) Thin Films on Area‐Enhanced Substrates

Abstract: Low‐grade heat sources are abundant yet challenging to use for energy harvesting. Herein, the pyroelectric effect in Si‐doped HfO2 thin films is used to demonstrate thermal‐electric energy conversion. The 20 nm thin films are grown on an area‐enhanced substrate via atomic layer deposition, which enhances the power output by a factor of 19 in comparison to planar materials. Ferroelectric and pyroelectric properties of the Si‐doped HfO2 are investigated, and a large pyroelectric coefficient of –1442 μC m−2 K−1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 40 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…The possibility for nand p-type FeFETs [5] enables in addition a larger freedom for novel circuit designs. Moreover, this material system has spurred attention in other applications, like neuromorphic devices [6][7][8], energy harvesting [9,10], sensors and actuators [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility for nand p-type FeFETs [5] enables in addition a larger freedom for novel circuit designs. Moreover, this material system has spurred attention in other applications, like neuromorphic devices [6][7][8], energy harvesting [9,10], sensors and actuators [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…One solution for increasing the sensor current is to use an array of pyroelectric sensors, as discussed earlier, or a micromachined Si array (see Figure 27), of tens of millions of trenches. [50][51][52] In the last case, a current of few nA is generated when changing the temperature between 29 and 31 C. The ECE effect was also termed as giant in the case of Hf ZrO, raising the hope for miniaturized solid-state refrigerators, which are key components in many industries where heat is produced. In particular, such devices are of interest for microprocessors, where for many years the dissipated heat is the main obstacle to increase significantly the performances.…”
Section: Energy Harvesting Using Hfo 2 -Based Ferroelectricsmentioning
confidence: 99%
“…One solution for increasing the sensor current is to use an array of pyroelectric sensors, as discussed earlier, or a micromachined Si array (see Figure ), of tens of millions of trenches. [ 50–52 ] In the last case, a current of few nA is generated when changing the temperature between 29 and 31 °C.…”
Section: Energy Harvesting Using Hfo2‐based Ferroelectricsmentioning
confidence: 99%
“…Recently, it was reported that the TiN/Si:HfO 2 /TiN structure deposited on the area-enhanced silicon substrate exhibited a large pyroelectric coefficient (−1442 μC/m 2 K). 147…”
Section: Hfo 2 -Based Infrared Sensorsmentioning
confidence: 99%
“…Additionally, the pyroelectric coefficient of the HfO 2 thin films can be further improved by the deposition of metal/insulator/metal structure on an area-enhanced silicon substrate. Recently, it was reported that the TiN/Si:HfO 2 /TiN structure deposited on the area-enhanced silicon substrate exhibited a large pyroelectric coefficient (−1442 μC/m 2 K) …”
Section: Hfo2-based Infrared Sensorsmentioning
confidence: 99%